Modern RF and Microwave Filter Design. - Bhartia, Prakash (Engineering professional collection, 2016)
This authoritative resource presents current practices for the design of RF and microwave filters. This one-stop reference provides readers with essential and practical information in order to design their own filter design software package, ultimately saving time and money. Essential building blocks for each type of filter are presented including network theory, transmission lines, and coupling mechanisms. This book presents a detailed discussion of the Low Pass Filter prototype, which is then extended to other configurations such as high pass, band pass, band stop, diplexers, and multiplexers. Microwave Network Theory and Transmission Line Coupling Mechanisms are presented along with a comprehensive discussion of the characteristics of commonly used transmission lines such as waveguides, Striplines, and Microstrip lines. Numerous design examples are presented to demonstrate an inclusive design methodology.